Electrodeposition of Aluminum onto Copper-Coated Printed Circuit Boards. Issue 12 (1st January 2017) - Xu, Min; Yue, Guikuan; Bizzotto, Dan; Asselin, Edouard
Abstract : The electrodeposition of aluminum thin films onto copper-coated printed circuit boards from aluminum chloride-trimethylphenylammonium chloride ionic liquids is studied. Various electrodeposition methods with different surface pretreatment procedures were investigated and compared to optimize the deposited aluminum morphology and properties. For the same amount of charge, a pulse current deposition approach applied at a low duty cycle of 10% allowed the use of higher deposition current densities, leading to finer and more compact aluminum deposits compared with those produced by constant potential and constant current deposition techniques. Pulse current deposition with various peak current densities of −25 mA/cm 2 to −65 mA/cm 2 was conducted over a temperature range of 20°C to 60°C. At a moderate temperature of 40°C, the electrodeposited aluminum layer was the most adherent. An increase of peak current density did not have an obvious effect on the deposit morphology, but it led to an increased amount of both deposited aluminum and incorporated impurities (oxygen and chloride). At room temperature, the electrical resistivity of the copper-coated printed circuit boards with deposited aluminum decreased as the peak current density for aluminum deposition increased.